2004
DOI: 10.1093/brief-treatment/mhh001
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation as a Response to Community Disaster

Abstract: Public education is a means of supporting trauma survivors without impeding their natural recovery process by providing accurate information about normal reactions and ways to cope in the aftermath of community disaster. It can also be used to screen for high-risk individuals who could benefit from ongoing care. Normalizing trauma reactions and eliminating the hardship of seeking mental health resources may reduce the stigma associated with obtaining this type of support. One way to accomplish this is by linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Psycho-education was been a major response to terror-related community reactions (Howard & Goelitz, 2004). However, a review of the different materials revealed discrepancies in what is recommended to parents and teachers.…”
Section: Resultsmentioning
confidence: 99%
“…Psycho-education was been a major response to terror-related community reactions (Howard & Goelitz, 2004). However, a review of the different materials revealed discrepancies in what is recommended to parents and teachers.…”
Section: Resultsmentioning
confidence: 99%
“…(3) social support [e.g., (3,(39)(40)(41)(42)(43)(44)(45)]; (4) problem solving [e.g., (46,47)]; (5) cognitive restructuring/control [e.g., (36,(48)(49)(50)(51)(52)]; (6) psychoeducation [e.g., (53)(54)(55)(56)]; (7) activity scheduling and behavioural activation [e.g., (7,46,48,57,58)]; (8) healthy living and self-care [e.g., (7,59)]; and (9) mindfulness [e.g., (26,28)].…”
Section: Literature Scoping To Identify Mechanisms Of Recoverymentioning
confidence: 99%
“…Specific suggestions provided to staff during in-services and individual or unit debriefings are described in the following. Several suggestions were based on cognitive behavioral principles (e.g., thought-stopping; Bakker, 2009), coping strategies and reassurance offered in psycho-educational workshops (e.g., normalizing the reactions; Howard & Goelitz, 2004), or self-care strategies described in the ST/VT literature (e.g., exercise and relaxation strategies; Pearlman, 1999). Additional suggestions were included over time as the author and other staff members shared strategies that had been effective for them (e.g., voice mail messages with "to-do" lists; transition time from work to home).…”
Section: Self-care Suggestions For Staffmentioning
confidence: 99%